Inception and development of a LC-MS/MS assay for the multiplexed quantitation of nine human drug transporter biomarkers - Kadar, Eugene P; Holliman, Christopher L; Vourvahis, Manoli; Rodrigues, A David (Bioanalysis, 2024)
It has become common practice to assess solute carrier transporter (SLC)-mediated drug-drug interactions (DDIs) by quantitating various individual endogenous compounds as biomarkers in human plasma and urine. The goal of this work was to develop biomarker multiplex assays that could be utilized during first in human studies to support the simultaneous assessment of clinical DDI risk across various SLCs. Hydrophilic interaction chromatography-MS/MS methods were developed, and validations were performed. The multiplex assays were applied to a first in human study. Placebo/reference subject biomarker data were consistent with single assay in-house and published data. This work demonstrates the utility of these multiplex methods to support the concurrent evaluation of clinical DDI risk across various SLCs.